Polyacrylic acid-based carbon aerogel for fuel cells and method for preparing the same

CN122494688BActive Publication Date: 2026-10-09SUZHOU BOLAN SPACE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610966361.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-09
Estimated Expiration
2046-07-01

AI Technical Summary

Technical Problem

然而,现有碳气凝胶的制备方法通常涉及复杂的溶胶-凝胶过程,存在工艺流程繁琐、成本高、结构可控性差等问题

Benefits of technology

本发明通过采用芳纶纳米纤维分步增强聚丙烯酸改性策略,协同支化聚乙烯亚胺立体交联调控作用,相较于传统单一聚丙烯酸基碳气凝胶材料及常规线性聚合物复合改性技术,具备多项突出有益效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122494688B_ABST
    Figure CN122494688B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of fuel cell electrode material preparation, and particularly relates to a polyacrylic acid-based carbon aerogel for fuel cells and a preparation method thereof. The method comprises the following steps: (1) preparing an aramid nanofiber dispersion liquid; (2) preparing an aramid nanofiber primary gel, adding the aramid nanofiber primary gel into a polyacrylic acid aqueous solution, stirring uniformly, and then adding branched polyethylene imine to obtain a hydrogel; (3) drying to obtain an aerogel; and (4) high-temperature carbonization to obtain a polyacrylic acid-based carbon aerogel for fuel cells. The aramid nanofiber primary gel is used to reinforce the polyacrylic acid, the problem of easy agglomeration of directly added aramid nanofibers is solved, the branched polyethylene imine enhances the structural stability of the aerogel, the problems of easy collapse of the structure of a traditional polyacrylic acid-based carbon aerogel, insufficient strength and poor conductivity are solved, the polyacrylic acid-based carbon aerogel has excellent structural stability and good conductivity, and can be used as a fuel cell electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fuel cell electrode material preparation technology, specifically relating to a polyacrylic acid-based carbon aerogel for fuel cells and its preparation method. Background Technology

[0002] A fuel cell is a device that converts chemical energy into electrical energy through an electrochemical reaction. Besides hydrogen, its basic fuel types include methanol, ethanol, and ammonia. Among these, hydrogen fuel cells, using hydrogen as a reactant, have become the main type of fuel cell due to their high energy density and pollution-free reaction products. Traditional internal combustion engines, limited by the Carnot cycle, typically have a thermal efficiency below 40%. In contrast, fuel cells based on electrochemical reactions usually achieve a conversion efficiency of over 60%.

[0003] Currently, the most widely studied fuel cells are proton exchange membrane fuel cells (PEMFCs) and anion exchange membrane fuel cells (AEMFCs), which use polymer electrolytes as the membrane. Their working principle is basically the same as that of common batteries, with the core components being the anode, cathode, and electrolyte membrane. The difference lies in the fact that reactants in a fuel cell are continuously delivered into the cell, thus freeing the cell's capacity from volume limitations. The discharge performance of a fuel cell mainly depends on the quality of the anode and cathode catalysts. Currently, carbon electrode materials are the most widely studied electrode materials.

[0004] Traditional carbon electrode materials are predominantly microporous, offering high specific surface areas. However, under high current density conditions, the diffusion of reactants (oxygen / hydrogen / methanol) to the catalyst active sites is restricted, leading to increased concentration polarization and reduced catalyst utilization and battery output performance. Simultaneously, water generated during the catalytic reaction is difficult to drain promptly, easily causing "flooding" and further deteriorating mass transfer efficiency. Existing carbon materials primarily rely on template methods for pore structure control, resulting in complex, time-consuming, and costly preparation processes, and making precise design of multi-level pore structures from micropores to mesopores difficult. A single-scale pore structure cannot simultaneously meet the dual requirements of high specific surface area and rapid mass transfer. To address these issues, researchers have explored using novel carbon materials such as mesoporous carbon, carbon aerogels, carbon nanotubes, and graphene as catalyst supports. Among these, carbon aerogels, with their three-dimensional network structure, high specific surface area, tunable pore size distribution, and good conductivity, show potential as carbon electrode materials for fuel cells. However, existing carbon aerogel preparation methods typically involve complex sol-gel processes, resulting in cumbersome processes, high costs, and poor structural controllability.

[0005] Therefore, developing a carbon electrode material for fuel cells with controllable structure, high mass transfer efficiency, good conductivity, and simple preparation process, as well as its preparation method, is of great significance for promoting the advancement and application of fuel cell technology. Summary of the Invention

[0006] The purpose of this invention is to provide a polyacrylic acid-based carbon aerogel for fuel cells and its preparation method. The polyacrylic acid-based carbon aerogel provided by this invention has a large specific surface area, numerous active sites, low resistivity, and good conductivity. Furthermore, the preparation process is simple and suitable for industrial production.

[0007] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: A method for preparing polyacrylic acid-based carbon aerogel for fuel cells includes the following steps: (1) Add aramid fibers and alkali metal hydroxide to an organic solvent, then add deionized water dropwise, stir and disperse to obtain an aramid nanofiber dispersion; (2) Immerse the aramid nanofiber dispersion in deionized water and let it stand for 2-4 hours. Then add the formed primary gel to the polyacrylic acid aqueous solution, stir evenly, add branched polyethyleneimine, let it stand again, and exchange solvent with deionized water to obtain hydrogel; the mass ratio of branched polyethyleneimine to polyacrylic acid is (0.05-0.2):1. (3) Dry the hydrogel to obtain an aerogel; (4) The aerogel is carbonized at high temperature under inert gas protection, and then washed and dried to obtain a polyacrylic acid-based carbon aerogel for fuel cells.

[0008] Polyacrylic acid (PAA), as a readily available polymer precursor with excellent water solubility, has become one of the most widely used carbon sources in the preparation of carbon aerogels. Existing research shows that PAA molecules are rich in carboxyl groups, enabling them to smoothly complete the sol-gel transition through hydrogen bonding, forming a three-dimensional hydrogel network. Furthermore, PAA can undergo decarboxylation during pyrolysis under a high-temperature inert atmosphere, achieving self-templating pore formation and thus obtaining carbon aerogels with high specific surface area and well-developed pore structure. Simultaneously, PAA can be combined with other functional components through simple cross-linking modification or in-situ composites, facilitating the control of the pore size distribution, morphology, and surface chemical properties of carbon materials, demonstrating excellent potential for industrial applications.

[0009] However, the preparation of carbon aerogels using pure polyacrylic acid as a single carbon source still suffers from inherent defects that are difficult to overcome in existing technologies, severely limiting its use in applications such as fuel cells where high structural strength and stability are required. Pure polyacrylic acid molecules are flexible, and the resulting hydrogels rely solely on weak hydrogen bonds for cross-linking, resulting in extremely low mechanical strength. During post-processing such as solvent exchange and drying, significant shrinkage, cracking, and overall structural collapse are highly likely, making it impossible to maintain a continuous and stable three-dimensional porous network. Simultaneously, polyacrylic acid has poor thermal stability, undergoing violent thermal decomposition during high-temperature carbonization, easily leading to pore collapse, product powdering, and other problems. The resulting carbon aerogels are brittle, have poor structural integrity, and their conductivity is insufficient to meet the practical requirements of fuel cell electrodes. While existing technologies have attempted to modify and optimize polyacrylic acid-based carbon aerogels using crosslinking agents, inorganic nanoparticles, or other polymers to improve their structural stability, conventional modifying components struggle to construct a high-temperature-resistant, high-strength, continuous rigid framework. Their effectiveness in suppressing structural collapse during drying and carbonization, and in improving overall residual carbon content and pore structure retention, is limited, making it difficult to achieve a synergistic improvement in high specific surface area, excellent mechanical properties, and good electrocatalytic performance. More importantly, when using fillers to reinforce polyacrylic acid aerogels, existing technologies require on-site initiation of acrylic acid monomer polymerization. This process involves concentrated exothermic reactions and difficulty in precisely controlling the polymerization rate, easily leading to localized over-polymerization and incomplete polymerization. The resulting gel exhibits uneven network density and numerous inherent microscopic defects. Furthermore, the monomer polymerization process is susceptible to interference from ambient temperature, impurities, and oxygen, resulting in poor system stability and low batch-to-batch reproducibility, hindering large-scale stable preparation. Moreover, the pure polymer network formed by in-situ polymerization relies on the entanglement of single molecular chains to form a structure without rigid framework support. This results in weak mechanical strength, poor thermal stability, and high drying shrinkage. The framework is also prone to collapse during carbonization, ultimately leading to disordered pores and poor structural integrity in the carbon aerogel, resulting in insufficient reliability of the electrode during service.

[0010] To address the problems of complex synthesis processes, low mechanical strength, poor thermal stability, and easy structural collapse and breakage after carbonization of polyacrylic acid aerogels, this invention employs aramid nanofibers as a reinforcing phase, abandoning in-situ polymerization processes and directly strengthening and optimizing the skeleton of the polyacrylic acid aerogel. Aramid nanofibers possess high strength, high modulus, and excellent thermal stability, forming a continuous, interconnected three-dimensional rigid support network within the polyacrylic acid gel system. This significantly improves the mechanical strength and structural stability of the composite system, effectively suppressing volume shrinkage and structural collapse during solvent exchange, drying, and carbonization. Aramid nanofibers exhibit high carbon residue under high-temperature carbonization conditions, enabling them to tightly bond with the carbon matrix formed by the pyrolysis of polyacrylic acid, improving the overall carbon residue and structural integrity of the system. This maintains a stable hierarchical porous structure in the carbonization products, increasing their surface area. Through the combined action of aramid nanofibers and polyacrylic acid, the resulting carbon aerogel possesses high specific surface area, good electrical conductivity, and excellent structural stability, better meeting the application requirements of fuel cell electrode materials.

[0011] In one embodiment, the organic solvent in step (1) is one or more of dimethyl sulfoxide (DMSO), dimethylformamide (DMF), and dimethylacetamide (DMAC). These solvents are all common polar aprotic organic solvents in the art, which can effectively promote fiber dispersion.

[0012] In one embodiment, the alkali metal hydroxide in step (1) is one or more of NaOH and KOH.

[0013] In one embodiment, the stirring in step (1) can be carried out at room temperature, and the stirring and dispersion time is 24-48h.

[0014] In one embodiment, the ratio of aramid fiber, alkali metal hydroxide, deionized water, and organic solvent in step (1) is 1g:(0.5-2)g:(1-3)mL:(50-150)mL. The concentration of the formed aramid nanofiber dispersion is not particularly limited, but can specifically be 0.1-5wt%. Further, it can be 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, or 5wt%. Specifically, the concentration of the aramid nanofiber dispersion is 0.5-1.5wt%.

[0015] In one embodiment, in step (2), the primary hydrogel is formed by standing for 2-4 hours, and then the prepared primary hydrogel is mixed with an aqueous solution of polyacrylic acid. Specifically, to facilitate the preparation of the primary hydrogel, the aramid nanofiber dispersion can be placed in an open mold and then immersed in deionized water to facilitate the sol-gelation process and solvent replacement. Furthermore, the aramid nanofiber dispersion can also be placed in deionized water with intermittent replacement to facilitate solvent replacement and further washing of the primary gel. The mold size is not particularly limited and can be adjusted according to the production scale. Specifically, an open mold with a volume of 4cm (length) × 4cm (width) × 2cm (height) can be used (i.e., a mold with a bottom and opening area of ​​4cm × 4cm and a height of 2cm). Further, in a specific embodiment, multiple sets of molds can be set simultaneously to prepare a large amount of primary gel for reinforcing polyacrylic acid.

[0016] To address the issue of uneven dispersion of aramid nanofibers in highly polar polyacrylic acid polymers, this invention first prepares aramid nanofibers into a primary hydrogel, which is then blended with polyacrylic acid, thus resolving the problem of easy agglomeration of aramid nanofibers upon direct addition. First, deionized water is introduced into the aramid nanofiber dispersion and allowed to stand for 2-4 hours. This causes a gradual change in the polar environment within the system, spontaneously forming numerous reversible, weakly interacting intermolecular hydrogen bonds between the abundant exposed hydroxyl, carboxyl, and amide groups on the surface of the aramid nanofibers. This constructs a loose, reversible primary physical gel precursor with a weak network constraint effect. This primary hydrogen bond network does not form a high-strength cross-linked structure; it only serves to spatially confine and stabilize the dispersion, effectively fixing the spatial distribution of the exfoliated aramid nanofibers and inhibiting van der Waals aggregation, chain entanglement, and local sedimentation and agglomeration of the nanofibers during solvent environment changes. This solves the problems of uneven dispersion and local agglomeration of aramid nanofibers during subsequent blending with polyacrylic acid polymers, providing a stable and monodisperse fiber matrix environment for uniform multi-component interfacial composites. Based on this, an aqueous solution of polyacrylic acid was added to the primary weak gel system and mechanically stirred. The shear force generated by stirring could directionally destroy the weak hydrogen bond primary network structure temporarily constructed in the early stage, release the spatial binding effect between fibers, and enable the originally fixed aramid nanofibers to regain flow compatibility. At the same time, the linear long-chain polyacrylic acid molecules fully expanded in the aqueous solution, interpenetrating, entangled and wetting the aramid nanofiber segments, realizing the homogeneous mixing of the two phases at the molecular scale, forming a thermodynamically stable, phase-separated and particle-free homogeneous composite aqueous solution system, which greatly improved the interfacial adhesion and compatibility of the two phases, and effectively avoided the technical problem of agglomeration caused by the direct addition of aramid nanofibers.

[0017] It is worth noting that this step requires controlling the settling time of the aramid nanofiber mixture solution. Controlling the settling time to 2-4 hours is crucial to adapt to the slow, reversible association kinetics of hydrogen bonds on the aramid nanofiber surface, smoothly constructing a uniform, loose, and easily disrupted primary weak hydrogen bond network. This ensures the monodisperse stability of the fibers and meets the requirements of the subsequent homogeneous composite molding process. If the settling time is too short, the solvent replacement is insufficient, the activation level of the polar groups on the aramid nanofiber surface is inadequate, and the fibers cannot uniformly overlap to form a complete primary confined network. The fibers remain in a free and disordered state, and the spatial confinement effect does not meet the process requirements. When polyacrylic acid aqueous solution is added and stirred, under the influence of solvent interfacial tension fluctuations and the superposition of intermolecular van der Waals forces, the free aramid nanofibers rapidly undergo large-scale secondary entanglement and localized agglomeration, resulting in regional fiber enrichment and component segregation and stratification. The two phases cannot achieve microscale uniform compatibility, directly causing uneven density and increased primary defects in the internal structure of the composite hydrogel. This leads to overall shrinkage during the subsequent drying stage. After high-temperature carbonization, the carbon skeleton in the agglomerated areas becomes densely packed with no effective mass transfer channels, while the weakly dispersed areas collapse and pulverize. Ultimately, the conductive network of the carbon electrode breaks down, and the multi-level porous structure is destroyed. If the standing time is too long, the weak hydrogen bonds between the aramid nanofibers continue to superimpose and cross-link, continuously associating and densifying. The originally loose and reversible primary soft gel gradually solidifies into a highly cross-linked rigid pre-formed gel, with a significant increase in network bonding strength. Subsequent conventional stirring shear forces cannot completely break up the hardened gel clumps; they can only break the surface structure, leaving the internal dense gel core intact. This core cannot interpenetrate and dissolve with the polyacrylic acid molecular chains, forming permanent interfacial phase separation hard defects. The subsequent molding of composite hydrogels resulted in severe stress concentration, easy deformation during drying, loss of rigid fiber skeleton during carbonization, stress collapse of local cross-linked structures, unbalanced overall residual carbon distribution, and disordered and impermeable pore arrangement. The final carbon aerogel had poor mechanical stability and insufficient structural integrity, and could not meet the core usage requirements of fuel cell electrodes for long-term cycling, stable conductivity, and efficient mass transfer.

[0018] In one embodiment, the stirring rate in step (2) is 400-800 rpm. Specifically, ultrasound may also be used to promote the dispersion of the components. The stirring rate is not particularly limited, but can be 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, or 800 rpm. Furthermore, the stirring rate can be 500-700 rpm. After adding the polyacrylic acid aqueous solution to the system, the primary weak hydrogen-bonded gel network formed in the early stage can be controlled to disintegrate by stirring, while ensuring uniform mixing and compatibility between the aramid nanofibers and the polyacrylic acid molecular chains.

[0019] In one embodiment, the type of branched polyethyleneimine in step (2) is not particularly limited. Specifically, branched polyethyleneimine with a weight-average molecular weight of 500-5000 can be selected. More specifically, at least one of the following weight-average molecular weights can be selected: 600 (PEI600), 800 (PEI 800), 1200 (PEI 1200), 1500 (PEI 1500), 1800 (PEI 1800), 2000 (PEI2000), 3000 (PEI 3000), 4000 (PEI 4000), and 5000 (PEI 5000). In particular, branched polyethyleneimine with a weight-average molecular weight of 1000-2000 can be selected. Branched polyethyleneimine with a suitable molecular weight can fully play the role of hydrogen bonding crosslinking, while avoiding the problems of excessive molecular weight, excessive steric hindrance, and difficulty in dispersion.

[0020] Branched polyethyleneimine is introduced into a homogeneous mixture. The surface of this polymer molecule is rich in high-density, multi-branched active amino groups, which can easily form hydrogen bonds or undergo dehydration reactions with oxygen-containing functional groups. It can serve as a multifunctional hydrogen bond or chemical bond crosslinking bridge. One end forms strong bonds with polar groups such as hydroxyl, carboxyl, and amide groups on the surface of aramid nanofibers, while the other end undergoes multi-site coordination crosslinking with high-density carboxyl functional groups on the polyacrylic acid molecular chain. Through bidirectional synchronous bonding and the interaction between aramid nanofibers and polyacrylic acid, a three-dimensional continuous, high-strength composite hydrogen bond or covalent bond network with controllable crosslinking density and strong interfacial bonding is reconstructed within the system. The stepwise hydrogen bond-controlled molding method of primary gelation and supplementation with polyacrylic acid adopted in this invention not only ensures that the aramid nanofibers are monodisperse and do not agglomerate throughout the process, but also achieves deep interfacial composite between the rigid fiber phase and the flexible polymer phase. The final result is a composite hydrogel with uniform structure, mechanical stability and continuous three-dimensional channels, which can withstand the harsh conditions of subsequent drying and dehydration and high-temperature full-process pyrolysis and carbonization. Relying on the high residual carbon rigid skeleton of aramid and the in-situ pore-forming advantage of polyacrylic acid, a high-performance carbon aerogel with well-developed multi-level pores, complete and stable structure and abundant nitrogen-doped active sites is finally prepared, which is suitable for the actual application requirements of electrode materials for fuel cells.

[0021] The reason this invention chooses branched polyethyleneimine instead of linear polyethyleneimine is that branched polyethyleneimine possesses a three-dimensional branched topology with high molecular spatial freedom, a dense and uniformly distributed number of terminal active amino groups, and the ability to achieve multi-directional, multi-site synchronous hydrogen bond bridging and crosslinking in aqueous solution. On one hand, its numerous high-density terminal amino groups can simultaneously form omnidirectional, multi-node synergistic hydrogen bonds or covalent bonds with the oxygen-containing polar groups on the surface of aramid nanofibers and the numerous carboxyl groups on the polyacrylic acid molecular chains. This results in abundant crosslinking sites and high crosslinking efficiency, enabling the rapid construction of a uniformly crosslinked, dense, and mechanically strong three-dimensional integrated composite gel network, effectively strengthening the interfacial bonding between the two phases and ensuring the regularity and integrity of the composite gel framework. On the other hand, the dendritic three-dimensional spatial structure has good spatial adaptability and is not prone to chain segment entanglement, stacking, or curling like linear linear molecules. It can be uniformly interwoven in the gaps between aramid nanofibers and polyacrylic acid molecules, avoiding defects such as excessive local crosslinking or blank local crosslinking, ensuring uniform crosslinking density throughout the gel, resulting in minimal subsequent drying shrinkage and structural deformation. In contrast, linear polyethyleneimine (PEI) has a one-dimensional linear molecular configuration, with active amino groups distributed along a single chain in limited numbers. It has few effective cross-linking sites and a single cross-linking direction, enabling only point-to-point linear overlap and failing to form a three-dimensional spatial cross-linking network. This results in low gel cross-linking strength and weak mechanical support. Furthermore, linear molecules are prone to self-entanglement and aggregation, leading to localized cross-linking accumulation, uneven interfacial bonding, and numerous microstructural defects. PII is unable to stably anchor aramid nanofibers and cannot effectively suppress skeletal slippage and pore collapse during subsequent carbonization, ultimately resulting in a loose carbon aerogel structure, poor pore connectivity, and insufficient mechanical stability, severely reducing the electrochemical performance of the electrode material.

[0022] In one embodiment, the mass ratio of polyacrylic acid and aramid nanofibers in step (2) is (15-25):1. By adjusting the amount of polyacrylic acid, it can be fully wetted and compatible with aramid nanofibers, and can also achieve uniform hydrogen bond crosslinking with branched polyethyleneimine. The resulting gel structure is regular and stable, with well-developed pores and a complete skeleton after carbonization, ultimately yielding a carbon aerogel electrode material for fuel cells with excellent comprehensive performance. Polyacrylic acid is added in the form of an aqueous solution. The amount of water is not particularly limited, as long as the components are fully and uniformly dispersed.

[0023] In one embodiment, the mass ratio of polyacrylic acid and aramid nanofibers in step (2) can be 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1, or 25:1; further, it can be (18-23):1. A suitable amount of aramid nanofibers can achieve both rigid framework support and uniform two-phase composite effects, resulting in a composite carbon aerogel precursor with regular structure, mechanical stability, and excellent mass transfer and electrical conductivity. If the amount of aramid nanofibers is too low, a continuous rigid support network cannot be constructed, resulting in weak shrinkage resistance of the composite gel and easy collapse of the carbonized framework; if the amount is too high, it easily causes fiber entanglement and agglomeration, and uneven component dispersion, leading to stress concentration and pore blockage within the gel, increasing material brittleness and hindering product performance improvement.

[0024] In one embodiment, the mass ratio of branched polyethyleneimine to polyacrylic acid in step (2) is (0.1-0.2):1. Specifically, it can be 0.10:1, 0.12:1, 0.14:1, 0.16:1, 0.18:1, or 0.20:1. Furthermore, the mass ratio of branched polyethyleneimine to polyacrylic acid is (0.15-0.20):1. By controlling the branched polyethyleneimine within a reasonable and optimal dosage range, the crosslinking density can be uniformly controlled, ensuring a strong bridging of the interface between aramid nanofibers and polyacrylic acid, constructing a complete and stable three-dimensional composite gel network, while avoiding the introduction of excess organic impurities and internal stress defects. This allows the precursor to maintain its structural integrity throughout the drying and carbonization process, ultimately yielding a high-quality carbon aerogel with well-developed pores, a stable skeleton, excellent conductivity, and abundant active sites.

[0025] In one embodiment, step (2) involves a second settling period followed by solvent exchange with deionized water, lasting for 1-5 days. This settling and solvent exchange further enhances the stability of the gel network and reduces the impact of unwanted impurities.

[0026] In one embodiment, the drying in step (3) is freeze drying or supercritical drying.

[0027] In one embodiment, the inert gas in step (4) is one or more of nitrogen, helium, and argon.

[0028] In one embodiment, the high-temperature carbonization temperature in step (4) is 800-1000℃; the high-temperature carbonization time is 1-3h. Specifically, the high-temperature carbonization temperature can be 800℃, 850℃, 900℃, 950℃, or 1000℃. Furthermore, the high-temperature carbonization temperature can be 850℃-950℃. When the carbonization temperature is too low, the overall pyrolysis energy supply is insufficient, the polymer pyrolysis is incomplete, it is difficult to form a through-hole multi-level pore structure, and the specific surface area of ​​the material is low; at the same time, the cross-linking carbonization degree of aramid nanofibers is insufficient, the macromolecular chains are not completely aromatized, the degree of graphitization of the carbon skeleton is low, and the intrinsic resistance is high. Under low temperature conditions, the heteroatom doping binding force is weak, the active sites are unstable, there are more organic residual components inside the structure, and it is impossible to construct efficient ion and electron transport channels. When the carbonization temperature is too high, the excessive thermal shock can cause the originally well-ordered three-dimensional porous framework to undergo excessive graphitization and shrinkage, resulting in the melting and closure of a large number of micropores and mesopores, collapse and densification of the hierarchical porous structure, and a decrease in the effective specific surface area. At the same time, the high temperature can cause excessive carbonization and embrittlement of the rigid framework of aramid nanofibers, increasing the number of internal carbon lattice defects, significantly increasing the brittleness of the material, and greatly reducing its mechanical toughness. By adjusting the carbonization temperature and carbonization time, it is possible to ensure the complete pyrolysis of polyacrylic acid and promote the appropriate graphitization of aramid nanofibers to construct a high-strength, highly conductive, continuous carbon framework. At the same time, an appropriate amount of stable nitrogen-doped active sites are precisely retained, and the hierarchical pore structure, conductive network, and catalytic active center are synergistically optimized. Finally, a composite carbon aerogel with complete structure, well-developed pores, excellent conductivity, and strong electrochemical stability is prepared.

[0029] In one embodiment, the heating rate for high-temperature carbonization in step (4) is 1-10℃ / min. Specifically, the heating rates for high-temperature carbonization are 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, and 10℃ / min. A suitable heating rate can achieve carbonization quickly while avoiding structural collapse caused by excessively rapid heating. The washing method is not particularly limited. Specifically, hydrochloric acid and deionized water can be used for washing.

[0030] On the other hand, this invention also provides a polyacrylic acid-based carbon aerogel for fuel cells prepared using the above method. The main raw materials used in the preparation process of this invention—aramid fiber, polyacrylic acid, branched polyethyleneimine, solvent, and alkaline hydroxide—are all common types in the art and can be prepared or purchased independently. For example, in this invention, the aramid fiber can be DuPont Kevlar 29, the polyacrylic acid can be Shandong Chint PAA, and the branched polyethyleneimine can be Shanghai Aladdin series, etc. This carbon aerogel electrode material not only has a high specific surface area but also high conductivity, showing broad application prospects. By introducing aramid nanofibers as a three-dimensional rigid framework into the polyacrylic acid gel system, the high strength, high modulus, and high thermal stability of aramid nanofibers significantly improve the structural strength of the composite aerogel, effectively suppressing volume shrinkage and pore collapse during solvent exchange, drying, and high-temperature carbonization processes, while simultaneously increasing the overall residual carbon rate of the system and ensuring the structural integrity of the carbon aerogel after carbonization. Aramid nanofibers can achieve in-situ nitrogen doping during carbonization, optimizing the surface active sites and conductivity of carbon materials. Combined with the hierarchical pore structure formed by in-situ pore creation through polyacrylic acid pyrolysis, carbon aerogels with high mechanical strength, well-developed pores, good stability, and excellent conductivity are finally obtained, which can meet the comprehensive requirements of fuel cell electrode materials.

[0031] Beneficial effects: This invention employs a stepwise reinforcement strategy for polyacrylic acid modification using aramid nanofibers, synergistically modulating the stereocrosslinking of branched polyethyleneimine. Compared to traditional single polyacrylic acid-based carbon aerogel materials and conventional linear polymer composite modification techniques, it possesses several outstanding and beneficial effects.

[0032] (1) This invention utilizes short-time static setting to construct a primary weak hydrogen bond network, effectively suppressing the secondary entanglement and aggregation of aramid nanofibers in an aqueous system, achieving uniform dispersion and composite of the rigid reinforcing phase and the flexible carbon source phase at the molecular scale, eliminating microscopic defects such as component segregation and weak interfacial bonding in traditional composite gels from the source, significantly improving the overall structural uniformity and mechanical support stability of composite hydrogels and aerogel precursors, and greatly reducing the risk of process scrap such as drying shrinkage and molding cracking.

[0033] (2) Aramid nanofibers have high thermal stability and high residual carbon properties. They can build a continuous and stable rigid three-dimensional support skeleton during the entire high-temperature carbonization process, effectively overcoming the inherent drawbacks of poor thermal stability and easy collapse of carbonization channels of pure polyacrylic acid. They can completely retain the multi-level interconnected porous structure, significantly improve the structural integrity and mechanical fatigue resistance of carbon aerogel, and meet the mechanical working conditions requirements of long-term assembly and cyclic service of fuel cell electrodes.

[0034] (3) Branched polyethyleneimine is used to replace the traditional linear crosslinking agent with a three-dimensional multi-point hydrogen bond crosslinking. The crosslinking site density is high and the spatial adaptability is strong. It can bridge the interface between aramid nanofibers and polyacrylic acid in both directions. The crosslinking network is uniform and dense without local stress concentration, which further strengthens the interface bonding strength of the composite system and avoids structural damage problems such as interface peeling and skeleton slippage during carbonization.

[0035] (4) During the carbonization process, aramid nanofibers provide stable nitrogen-doped active sites in situ, and polyacrylic acid pyrolysis provides abundant oxygen-doped functional groups and multi-level mass transfer channels. The two work together to construct a nitrogen-doped multidimensional conductive network, which effectively improves the intrinsic conductivity and oxygen reduction electrocatalytic activity of the material and reduces the polarization impedance of the electrode interface.

[0036] (5) The direct composite process of polyacrylic acid is adopted, which eliminates the complex process of adding acrylic acid monomers to the fiber to initiate the polymerization of hydrogels in situ, which is required in traditional processes. The overall preparation process of this invention is mild and highly controllable, without the need for additional high-temperature crosslinking, external dopants and complex post-processing. The raw materials are readily available, the process is simple, the batch repeatability is good, and it is suitable for large-scale batch preparation. It comprehensively solves the problems of easy collapse, insufficient strength, poor conductivity and low catalytic activity of traditional polyacrylic acid-based carbon electrode structures. The resulting carbon aerogel electrode material has excellent structural stability, high mass transfer capacity and good conductivity, and can be used as a fuel cell electrode material. Attached Figure Description

[0037] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0038] Figure 1 This is a scanning electron microscope image of the carbon aerogel prepared in Example 10 of the present invention.

[0039] Figure 2 This is a scanning electron microscope image of the carbon aerogel prepared in Comparative Example 1 of this invention.

[0040] Figure 3 This is a scanning electron microscope image of the carbon aerogel prepared in Comparative Example 2 of this invention.

[0041] Figure 4 This is a scanning electron microscope image of the carbon aerogel prepared in Comparative Example 3 of the present invention. Detailed Implementation

[0042] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the described embodiments of the present invention without creative effort are within the scope of protection of the present invention. Unless otherwise defined, the technical or scientific terms used herein should have the ordinary meaning understood by those skilled in the art to which this invention pertains.

[0043] Example 1

[0044] A method for preparing polyacrylic acid-based carbon aerogel for fuel cells includes the following steps: (1) Aramid fibers and KOH were dispersed in DMSO, and then deionized water was added dropwise. After stirring and dispersing for 28 hours, an aramid nanofiber dispersion was obtained; the ratio of aramid fibers, KOH, deionized water and DMSO was 1g:1.2g:2.2mL:100mL. (2) Place 10g of aramid nanofiber dispersion in a mold (volume 4cm×4cm×2cm), then immerse it in 2000mL of deionized water and let it stand for 2h. Add the formed primary gel to the polyacrylic acid aqueous solution, stir evenly at 650rpm, add branched polyethyleneimine PEI 800, disperse, and let it stand for 2 days. Then exchange solvent with deionized water to obtain hydrogel. The mass ratio of polyacrylic acid to aramid nanofiber is 17:1; the mass ratio of branched polyethyleneimine to polyacrylic acid is 0.05:1.

[0045] (3) Freeze-dry the hydrogel to obtain an aerogel; (4) The aerogel was carbonized at 900℃ for 2.5h under nitrogen protection, with a carbonization temperature rise rate of 2℃ / min. After washing and drying, a polyacrylic acid-based carbon aerogel for fuel cells was obtained. The specific surface area and conductivity of the carbon aerogel were tested using the BET method and a conductivity meter. The specific surface area was 1009 m². 2 g -1 The conductivity is 14.2 Scm. -1 .

[0046] Example 2

[0047] A method for preparing polyacrylic acid-based carbon aerogel for fuel cells includes the following steps: (1) Aramid fibers and KOH were dispersed in DMSO, and then deionized water was added dropwise. After stirring and dispersing for 36 hours, an aramid nanofiber dispersion was obtained. The ratio of aramid fibers, KOH, deionized water and DMSO was 1g:0.9g:2.2mL:100mL. (2) Place 10g of aramid nanofiber dispersion in a mold (volume 4cm×4cm×2cm), then immerse it in 2000mL of deionized water and let it stand for 4h. Add the formed primary gel to the polyacrylic acid aqueous solution, stir evenly at 650rpm, add branched polyethyleneimine PEI 1800, disperse, and let it stand for 3 days. Then exchange solvent with deionized water to obtain hydrogel. The mass ratio of polyacrylic acid to aramid nanofiber is 23:1; the mass ratio of branched polyethyleneimine to polyacrylic acid is 0.2:1.

[0048] (3) Freeze-dry the hydrogel to obtain an aerogel; (4) The aerogel was carbonized at 950℃ for 1.5h under nitrogen protection, with a carbonization temperature rise rate of 5℃ / min. After washing and drying, a polyacrylic acid-based carbon aerogel for fuel cells was obtained. The specific surface area and conductivity of the carbon aerogel were tested using the BET method and a conductivity meter. The specific surface area was 896 m². 2 g -1 The conductivity is 11.4 Scm -1 .

[0049] Example 3

[0050] A method for preparing polyacrylic acid-based carbon aerogel for fuel cells includes the following steps: (1) Aramid fibers and KOH were dispersed in DMSO, and then deionized water was added dropwise. After stirring and dispersing for 36 hours, an aramid nanofiber dispersion was obtained. The ratio of aramid fibers, KOH, deionized water and DMSO was 1g:1g:2.2mL:100mL. (2) Place 10g of aramid nanofiber dispersion in a mold (volume 4cm×4cm×2cm), then immerse it in 2000mL of deionized water and let it stand for 3h. Add the formed primary gel to the polyacrylic acid aqueous solution, stir evenly at 650rpm, add branched polyethyleneimine PEI 3000, disperse, and let it stand for 2.5 days. Then exchange solvent with deionized water to obtain hydrogel. The mass ratio of polyacrylic acid to aramid nanofiber is 20:1; the mass ratio of branched polyethyleneimine to polyacrylic acid is 0.15:1.

[0051] (3) Freeze-dry the hydrogel to obtain an aerogel; (4) The aerogel was carbonized at 930℃ for 2 hours under nitrogen protection, with a carbonization temperature rise rate of 4℃ / min. After washing and drying, a polyacrylic acid-based carbon aerogel for fuel cells was obtained. The specific surface area and conductivity of the carbon aerogel were tested using the BET method and a conductivity meter. The specific surface area was 961 m². 2 g -1 The conductivity is 13.2 Scm. -1 .

[0052] Example 4

[0053] A method for preparing polyacrylic acid-based carbon aerogel for fuel cells includes the following steps: (1) Aramid fibers and KOH were dispersed in DMSO, and then deionized water was added dropwise. After stirring and dispersing for 28 hours, an aramid nanofiber dispersion was obtained; the ratio of aramid fibers, KOH, deionized water and DMSO was 1g:0.9g:2.2mL:100mL. (2) Place 10g of aramid nanofiber dispersion in a mold (volume 4cm×4cm×2cm), then immerse it in 2000mL of deionized water and let it stand for 2.2h. Add the formed primary gel to the polyacrylic acid aqueous solution, stir evenly at 650rpm, add branched polyethyleneimine PEI 1200, disperse, and let it stand for 2 days. Then exchange solvent with deionized water to obtain hydrogel. The mass ratio of polyacrylic acid to aramid nanofiber is 18:1; the mass ratio of branched polyethyleneimine to polyacrylic acid is 0.1:1.

[0054] (3) Freeze-dry the hydrogel to obtain an aerogel; (4) The aerogel was carbonized at 920℃ for 2.5h under nitrogen protection, with a carbonization temperature rise rate of 3℃ / min. After washing and drying, a polyacrylic acid-based carbon aerogel for fuel cells was obtained. The specific surface area and conductivity of the carbon aerogel were tested using the BET method and a conductivity meter. The specific surface area was 922 m². 2 g -1 The conductivity is 14.5 Scm -1 .

[0055] Example 5

[0056] A method for preparing polyacrylic acid-based carbon aerogel for fuel cells includes the following steps: (1) Aramid fibers and KOH were dispersed in DMSO, and then deionized water was added dropwise. After stirring and dispersing for 36 hours, an aramid nanofiber dispersion was obtained. The ratio of aramid fibers, KOH, deionized water and DMSO was 1g:1g:2.2mL:100mL. (2) Place 10g of aramid nanofiber dispersion in a mold (volume 4cm×4cm×2cm), then immerse it in 2000mL of deionized water and let it stand for 3h. Add the formed primary gel to the polyacrylic acid aqueous solution, stir evenly at 650rpm, add branched polyethyleneimine PEI 1200, disperse, and let it stand for 2.5 days. Then exchange solvent with deionized water to obtain hydrogel. The mass ratio of polyacrylic acid to aramid nanofiber is 20:1; the mass ratio of branched polyethyleneimine to polyacrylic acid is 0.15:1.

[0057] (3) Freeze-dry the hydrogel to obtain an aerogel; (4) The aerogel was carbonized at 930℃ for 2 hours under nitrogen protection, with a carbonization temperature rise rate of 4℃ / min. After washing and drying, a polyacrylic acid-based carbon aerogel for fuel cells was obtained. The specific surface area and conductivity of the carbon aerogel were tested using the BET method and a conductivity meter. The specific surface area was 10¹⁴ m². 2 g -1 The conductivity is 15.8 Scm. -1 .

[0058] Example 6

[0059] A method for preparing polyacrylic acid-based carbon aerogel for fuel cells includes the following steps: (1) Aramid fibers and KOH were dispersed in DMSO, and then deionized water was added dropwise. After stirring and dispersing for 36 hours, an aramid nanofiber dispersion was obtained. The ratio of aramid fibers, KOH, deionized water and DMSO was 1g:1.2g:2.2mL:100mL. (2) Place 10g of aramid nanofiber dispersion in a mold (volume 4cm×4cm×2cm), then immerse it in 2000mL of deionized water and let it stand for 2.5h. Add the formed primary gel to the polyacrylic acid aqueous solution, stir evenly at 650rpm, add branched polyethyleneimine PEI 800, disperse, and let it stand for another 2.5 days to exchange solvent with deionized water to obtain hydrogel; the mass ratio of polyacrylic acid to aramid nanofiber is 19:1; the mass ratio of branched polyethyleneimine to polyacrylic acid is 0.12:1.

[0060] (3) Freeze-dry the hydrogel to obtain an aerogel; (4) The aerogel was carbonized at 910℃ for 2 hours under nitrogen protection, with a carbonization temperature rise rate of 2℃ / min. After washing and drying, a polyacrylic acid-based carbon aerogel for fuel cells was obtained. The specific surface area and conductivity of the carbon aerogel were tested using the BET method and a conductivity meter. The specific surface area was 913 m². 2 g -1 The conductivity is 12.9 Scm -1 .

[0061] Example 7

[0062] A method for preparing polyacrylic acid-based carbon aerogel for fuel cells includes the following steps: (1) Aramid fibers and KOH were dispersed in DMSO, and then deionized water was added dropwise. After stirring and dispersing for 36 hours, an aramid nanofiber dispersion was obtained. The ratio of aramid fibers, KOH, deionized water and DMSO was 1g:1g:2.2mL:100mL. (2) Place 10g of aramid nanofiber dispersion in a mold (volume 4cm×4cm×2cm), then immerse it in 2000mL of deionized water and let it stand for 3h. Add the formed primary gel to the polyacrylic acid aqueous solution, stir evenly at 650rpm, add branched polyethyleneimine PEI 1200, disperse, and let it stand for 2.5 days. Then exchange solvent with deionized water to obtain hydrogel. The mass ratio of polyacrylic acid to aramid nanofiber is 15:1; the mass ratio of branched polyethyleneimine to polyacrylic acid is 0.15:1.

[0063] (3) Freeze-dry the hydrogel to obtain an aerogel; (4) The aerogel was carbonized at 930℃ for 2 hours under nitrogen protection, with a carbonization temperature rise rate of 4℃ / min. After washing and drying, a polyacrylic acid-based carbon aerogel for fuel cells was obtained. The specific surface area and conductivity of the carbon aerogel were tested using the BET method and a conductivity meter. The specific surface area was 968 m². 2 g -1 The conductivity is 15.2 Scm. -1 .

[0064] Example 8

[0065] A method for preparing polyacrylic acid-based carbon aerogel for fuel cells includes the following steps: (1) Aramid fibers and KOH were dispersed in DMSO, and then deionized water was added dropwise. After stirring and dispersing for 36 hours, an aramid nanofiber dispersion was obtained; the ratio of aramid fibers, KOH, deionized water and DMSO was 1g:1.1g:2.2mL:100mL. (2) Place 10g of aramid nanofiber dispersion in a mold (volume 4cm×4cm×2cm), then immerse it in 2000mL of deionized water and let it stand for 3.5h. Add the formed primary gel to the polyacrylic acid aqueous solution, stir evenly at 650rpm, add branched polyethyleneimine PEI 1800, disperse, and let it stand for 3 days. Then exchange solvent with deionized water to obtain hydrogel. The mass ratio of polyacrylic acid to aramid nanofiber is 22:1; the mass ratio of branched polyethyleneimine to polyacrylic acid is 0.14:1.

[0066] (3) Freeze-dry the hydrogel to obtain an aerogel; (4) The aerogel was carbonized at 940℃ for 1.5h under nitrogen protection, with a carbonization temperature rise rate of 3℃ / min. After washing and drying, a polyacrylic acid-based carbon aerogel for fuel cells was obtained. The specific surface area and conductivity of the carbon aerogel were tested using the BET method and a conductivity meter. The specific surface area was 981 m². 2 g -1 The conductivity is 13.7 Scm. -1 .

[0067] Example 9

[0068] A method for preparing polyacrylic acid-based carbon aerogel for fuel cells includes the following steps: (1) Aramid fibers and KOH were dispersed in DMSO, and then deionized water was added dropwise. After stirring and dispersing for 28 hours, an aramid nanofiber dispersion was obtained. The ratio of aramid fibers, KOH, deionized water and DMSO was 1g:1.1g:2.2mL:100mL. (2) Place 10g of aramid nanofiber dispersion in a mold (volume 4cm×4cm×2cm), then immerse it in 2000mL of deionized water and let it stand for 3.2h. Add the formed primary gel to the polyacrylic acid aqueous solution, stir evenly at 650rpm, add branched polyethyleneimine PEI 600, disperse, and let it stand for 2.5 days. Then exchange solvent with deionized water to obtain hydrogel. The mass ratio of polyacrylic acid to aramid nanofiber is 21:1; the mass ratio of branched polyethyleneimine to polyacrylic acid is 0.18:1.

[0069] (3) Freeze-dry the hydrogel to obtain an aerogel; (4) The aerogel was carbonized at 920℃ for 2 hours under nitrogen protection, with a carbonization temperature rise rate of 5℃ / min. After washing and drying, a polyacrylic acid-based carbon aerogel for fuel cells was obtained. The specific surface area and conductivity of the carbon aerogel were tested using the BET method and a conductivity meter. The specific surface area was 938 m². 2 g -1 The conductivity is 13.2 Scm. -1 .

[0070] Example 10

[0071] A method for preparing polyacrylic acid-based carbon aerogel for fuel cells includes the following steps: (1) Aramid fibers and KOH were dispersed in DMSO, and then deionized water was added dropwise. After stirring and dispersing for 36 hours, an aramid nanofiber dispersion was obtained. The ratio of aramid fibers, KOH, deionized water and DMSO was 1g:1g:2.2mL:100mL. (2) Place 10g of aramid nanofiber dispersion in a mold (volume 4cm×4cm×2cm), then immerse it in 2000mL of deionized water and let it stand for 3h. Add the formed primary gel to the polyacrylic acid aqueous solution, stir evenly at 650rpm, add branched polyethyleneimine PEI 600, disperse, and let it stand for 2.5 days. Then exchange solvent with deionized water to obtain hydrogel. The mass ratio of polyacrylic acid to aramid nanofiber is 20:1; the mass ratio of branched polyethyleneimine to polyacrylic acid is 0.15:1.

[0072] (3) Freeze-dry the hydrogel to obtain an aerogel; (4) The aerogel was carbonized at 930℃ for 2 hours under nitrogen protection, with a carbonization temperature rise rate of 4℃ / min. After washing and drying, a polyacrylic acid-based carbon aerogel for fuel cells was obtained. The specific surface area and conductivity of the carbon aerogel were tested using the BET method and a conductivity meter. The specific surface area was 943 m². 2 g -1 The conductivity is 12.4 Scm. -1 .

[0073] Comparative Example 1 A method for preparing polyacrylic acid-based carbon aerogel for fuel cells includes the following steps: (1) Aramid fibers and KOH were dispersed in DMSO, and then deionized water was added dropwise. After stirring and dispersing for 36 hours, an aramid nanofiber dispersion was obtained. The ratio of aramid fibers, KOH, deionized water and DMSO was 1g:1g:2.2mL:100mL. (2) Take 10g of aramid nanofiber dispersion, filter, wash and disperse in deionized water to obtain aramid nanofiber aqueous dispersion, add aramid nanofiber aqueous dispersion directly to polyacrylic acid aqueous solution, stir evenly at 650rpm and add branched polyethyleneimine PEI 600, disperse and let stand for 2.5 days, exchange solvent with deionized water to obtain hydrogel; the mass ratio of polyacrylic acid to aramid nanofiber is 20:1; the mass ratio of branched polyethyleneimine to polyacrylic acid is 0.15:1.

[0074] (3) Freeze-dry the hydrogel to obtain an aerogel; (4) The aerogel was carbonized at 930℃ for 2 hours under nitrogen protection, with a carbonization temperature rise rate of 4℃ / min. After washing and drying, a polyacrylic acid-based carbon aerogel for fuel cells was obtained. The specific surface area and conductivity of the carbon aerogel were tested using the BET method and a conductivity meter. The specific surface area was 623 m². 2 g -1 The conductivity is 1.3 Scm. -1 .

[0075] Comparative Example 2 A method for preparing polyacrylic acid-based carbon aerogel for fuel cells includes the following steps: (1) Aramid fibers and KOH were dispersed in DMSO, and then deionized water was added dropwise. After stirring and dispersing for 36 hours, an aramid nanofiber dispersion was obtained. The ratio of aramid fibers, KOH, deionized water and DMSO was 1g:1g:2.2mL:100mL. (2) Place 10g of aramid nanofiber dispersion in a mold (volume 4cm×4cm×2cm), then immerse it in 2000mL of deionized water and let it stand for 8h. Add the formed primary gel to the polyacrylic acid aqueous solution, stir evenly at 650rpm, add branched polyethyleneimine PEI 600, disperse, and let it stand for 2.5 days. Then exchange solvent with deionized water to obtain hydrogel. The mass ratio of polyacrylic acid to aramid nanofiber is 20:1; the mass ratio of branched polyethyleneimine to polyacrylic acid is 0.15:1.

[0076] (3) Freeze-dry the hydrogel to obtain an aerogel; (4) The aerogel was carbonized at 930℃ for 2 hours under nitrogen protection, with a carbonization temperature rise rate of 4℃ / min. After washing and drying, a polyacrylic acid-based carbon aerogel for fuel cells was obtained. The specific surface area and conductivity of the carbon aerogel were tested using the BET method and a conductivity meter. The specific surface area was 695 m². 2 g -1 The conductivity is 3.5 Scm -1 .

[0077] Comparative Example 3 A method for preparing polyacrylic acid-based carbon aerogel for fuel cells includes the following steps: (1) Aramid fibers and KOH were dispersed in DMSO, and then deionized water was added dropwise. After stirring and dispersing for 36 hours, an aramid nanofiber dispersion was obtained. The ratio of aramid fibers, KOH, deionized water and DMSO was 1g:1g:2.2mL:100mL. (2) Place 10g of aramid nanofiber dispersion in a mold (volume 4cm×4cm×2cm), then immerse it in 2000mL of deionized water and let it stand for 3h. Add the formed primary gel to the polyacrylic acid aqueous solution, stir evenly at 650rpm, add branched polyethyleneimine PEI 600, disperse, and let it stand for 2.5 days. Then exchange solvent with deionized water to obtain hydrogel. The mass ratio of polyacrylic acid to aramid nanofiber is 20:1; the mass ratio of branched polyethyleneimine to polyacrylic acid is 0.4:1.

[0078] (3) Freeze-dry the hydrogel to obtain an aerogel; (4) The aerogel was carbonized at 930℃ for 2 hours under nitrogen protection, with a carbonization temperature rise rate of 4℃ / min. After washing and drying, a polyacrylic acid-based carbon aerogel for fuel cells was obtained. The specific surface area and conductivity of the carbon aerogel were tested using the BET method and a conductivity meter. The specific surface area was 734 m². 2 g -1 The conductivity is 3.2 Scm. -1 .

[0079] As can be seen from the above examples and comparative examples, to address the problems of complex synthesis process, low mechanical strength, poor thermal stability, and easy structural collapse and breakage after carbonization of polyacrylic acid aerogel, this invention uses aramid nanofibers as a reinforcing phase, abandoning the in-situ polymerization process and directly strengthening and optimizing the skeleton of polyacrylic acid aerogel. Aramid nanofibers possess high strength, high modulus, and excellent thermal stability, forming a continuous, interconnected three-dimensional rigid support network in the polyacrylic acid gel system, significantly improving the mechanical strength and structural stability of the composite system, and effectively suppressing volume shrinkage and structural collapse during solvent exchange, drying, and carbonization. Aramid nanofibers exhibit high residual carbon rate under high-temperature carbonization conditions, enabling them to tightly bond with the carbon matrix formed by the pyrolysis of polyacrylic acid, improving the overall residual carbon rate and structural integrity of the system, and maintaining a stable hierarchical porous structure in the carbonization products. Under the combined action of aramid nanofibers and polyacrylic acid, the final carbon aerogel obtained by carbonization possesses high specific surface area, good conductivity, and excellent structural stability, better meeting the application requirements of fuel cell electrode materials.

[0080] in, Figure 1 The image shows a scanning electron microscope (SEM) image of the carbon aerogel prepared in Example 10. As can be seen from the image, the carbon aerogel material constructs a complete and continuous three-dimensional interconnected porous network with well-developed hierarchical pores and a uniform pore size distribution. The overall structure is uniform, indicating that there were no obvious shrinkage cracks or large-size structural defects during the drying and carbonization processes. Furthermore, the carbon aerogel's carbon skeleton has a rough surface with abundant wrinkles, providing ample reactive sites. The overall structure shows no collapse or obvious cracks, exhibiting excellent skeleton regularity and structural integrity, providing a good microstructural foundation for efficient mass transfer, stable conductivity, and long-term service of the electrode.

[0081] Figure 2 The image shows a scanning electron microscope (SEM) image of the carbon aerogel prepared in Comparative Example 1. In Comparative Example 1, compared to Example 10, the aramid nanofibers were not prepared as a primary gel but were directly added to the polyacrylic acid solution. Figure 2 It can be seen that the corresponding carbon aerogel structure has blocked and disordered pores, and the overall three-dimensional porous network regularity and structural integrity are significantly reduced. This is because when aramid nanofibers are directly added, they are unevenly dispersed in the polyacrylic acid solution, easily agglomerate, and cannot interpenetrate and mix with the polyacrylic acid molecular chains, forming permanent interfacial phase separation hard defects. The subsequent molding of the composite hydrogel results in severe stress concentration, easy deformation during drying, loss of rigid fiber skeleton during carbonization, stress collapse of local cross-linked structures, and an unbalanced distribution of overall residual carbon. The final carbon aerogel has poor mechanical stability and insufficient structural integrity, and cannot meet the core application requirements of fuel cell electrodes for long-term cycling, stable conductivity, and efficient mass transfer. Figure 3 and Figure 4The images show the scanning electron microscope (SEM) images of carbon aerogels corresponding to Comparative Example 2 and Comparative Example 3, respectively. As can be seen from the images, although the pore structure has been improved to a certain extent compared with Comparative Example 1, the pore density is uneven, and there are local skeleton collapses, pore deformities, and irregular porous structures.

[0082] The specific data also show that the embodiments of the present invention first prepare aramid nanofibers into a primary hydrogel, and then blend it with polyacrylic acid, which solves the problem of easy agglomeration of aramid nanofibers. Compared with Example 10, Comparative Example 1 directly adds aramid nanofibers to the polyacrylic acid solution, resulting in uneven dispersion, inability to effectively build a reinforcing network, poor gel structure stability, collapse during drying and carbonization, inability to build a conductive network, and a significant reduction in specific surface area and conductivity.

[0083] Meanwhile, as can be seen from Comparative Examples 2 and 3, although the specific surface area of ​​the carbon aerogels prepared therein was improved to a certain extent compared with Comparative Example 1, their electrical conductivity was still low.

[0084] Specifically, in Comparative Example 2, the prolonged standing time during the preparation of the primary gel caused the weak hydrogen bonds between aramid nanofibers to continuously overlap, crosslink, and associate, leading to densification. The originally loose and reversible primary soft gel gradually solidified into a highly crosslinked, rigid pre-gel. Subsequent stirring and shearing forces could not completely break up the hardened gel clumps, only breaking the surface structure. The dense internal gel core remained intact and could not interpenetrate and dissolve with the polyacrylic acid molecular chains, forming permanent interfacial phase separation defects. The subsequent molding of the composite hydrogel resulted in severe stress concentration, easy deformation during drying, and damage to the rigid fiber skeleton and stress collapse of local crosslinked structures during carbonization. The final carbon aerogel had poor mechanical stability, insufficient structural integrity, and reduced conductivity. Compared with Example 10, Comparative Example 3 used too much branched polyethyleneimine, resulting in excessive accumulation of a large number of excess branched molecules in the system. This caused an increase in local crosslinking density, forming local high-density crosslinking agglomerates, while the crosslinking in other areas was relatively poor. This led to uneven crosslinking distribution in the entire gel system, generating a large number of residual internal stresses and micro-stress concentration points, which damaged the uniformity and compatibility of the composite system. As a result, the gel became too rigid and less tough, making it prone to brittleness during drying and carbonization. This also disrupted the orderly arrangement of the multi-level pore structure of the carbon aerogel, and its specific surface area and electrical conductivity decreased to a certain extent.

[0085] This demonstrates that the stepwise controlled molding method of primary gelation and supplementary polyacrylic acid adopted in this invention not only ensures that the aramid nanofibers are monodisperse and do not agglomerate throughout the process, but also achieves deep interfacial composite between the rigid fiber phase and the flexible polymer phase. The final result is a composite hydrogel with uniform structure, mechanical stability, and continuous three-dimensional channels, which can withstand the harsh conditions of subsequent drying and dehydration and high-temperature full-process pyrolysis and carbonization. Relying on the high residual carbon rigid skeleton of aramid and the in-situ pore-forming advantage of polyacrylic acid, a high-performance carbon aerogel with well-developed multi-level pores, complete and stable structure, and abundant nitrogen-doped active sites is finally prepared. It has a large specific surface area and high conductivity, which is suitable for the actual application requirements of electrode materials for fuel cells.

[0086] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing polyacrylic acid-based carbon aerogel for fuel cells, characterized in that, Includes the following steps: (1) Add aramid fibers and alkali metal hydroxide to an organic solvent, then add deionized water dropwise, stir and disperse to obtain an aramid nanofiber dispersion; the organic solvent is one or more of dimethyl sulfoxide, dimethylformamide, and dimethylacetamide; (2) Immerse the aramid nanofiber dispersion in deionized water and let it stand for 2-4 hours. Then add the formed primary gel to the polyacrylic acid aqueous solution, stir evenly, add branched polyethyleneimine, let it stand again, and exchange solvent with deionized water to obtain hydrogel; the mass ratio of branched polyethyleneimine to polyacrylic acid is (0.05-0.2):1; the mass ratio of polyacrylic acid to aramid nanofiber is (15-25):1; (3) Dry the hydrogel to obtain an aerogel; (4) The aerogel is carbonized at high temperature under the protection of inert gas, and then washed and dried to obtain a polyacrylic acid-based carbon aerogel for fuel cells; the high temperature carbonization temperature is 800-1000℃; the high temperature carbonization time is 1-3h.

2. The method for preparing polyacrylic acid-based carbon aerogel for fuel cells as described in claim 1, characterized in that, In step (1), the alkali metal hydroxide is one or more of NaOH and KOH.

3. The method for preparing polyacrylic acid-based carbon aerogel for fuel cells as described in claim 1, characterized in that, The stirring and dispersion time in step (1) is 24-48 hours.

4. The method for preparing polyacrylic acid-based carbon aerogel for fuel cells as described in claim 1, characterized in that, In step (2), the mass ratio of branched polyethyleneimine to polyacrylic acid is (0.1-0.2):

1.

5. The method for preparing polyacrylic acid-based carbon aerogel for fuel cells as described in claim 1, characterized in that, In step (3), the drying process is either freeze-drying or supercritical drying.

6. The method for preparing polyacrylic acid-based carbon aerogel for fuel cells as described in claim 1, characterized in that, In step (4), the inert gas is one or more of nitrogen, helium, and argon.

7. A polyacrylic acid-based carbon aerogel for fuel cells, characterized in that, It is prepared by the method for preparing a polyacrylic acid-based carbon aerogel for fuel cells according to any one of claims 1-6.

Citation Information

Patent Citations

  • Polyacrylonitrile nanometer fiber / polyimide-based composite carbon aerogel electrode material and preparation method thereof

    CN105845455A

  • Carbon electrode material for polypyrrole modified nylon-based fuel cell and preparation method of carbon electrode material

    CN120453398A